Spatial probabilities of eruption scenarios : a case study of the Auckland Volcanic Field, New Zealand - Ang, Pei Shan (2019)
Monogenetic volcanic fields, where the location of the next eruptive vent is not known, pose unique challenges to hazard managers. This is further compounded by the lack of knowledge on possible eruption styles at a location. Previous key forecasting methods to improve hazard management include probabilistic and scenario-based approaches. However, probabilistic approaches do not usually involve forecasts of future eruption style and scenario-based approaches tend to focus only on one location per scenario. Our study introduces the novel combined probabilistic-scenario approach, where probabilities will be used to determine locations where scenarios with varying eruptive styles are most likely to occur. This is applied to the Auckland Volcanic Field (AVF), which houses New Zealand’s largest city.